Studi Pengaruh Keterampilan Manajemen Keuangan Terhadap Kesuksesan Usaha Mahasiswa: Menggali Peran Motivasi Berwirausaha - Romansyah Sahabuddin; Hery Maulana Arif; Nuralisa; Putri Aliyah Natasya; M Nizar Aswat (Journal Management & Economics Review (JUMPER), 2024)
This study aims to analyze the influence of financial management skills on the success of students' businesses in Makassar City, with entrepreneurial motivation as an intervening variable. In the era of globalization, students' interest in entrepreneurship is increasing, but many fail to achieve success due to lack of financial skills. Using a causal method with a quantitative approach, this study involved 105 students who run independent businesses. The results of the analysis show that financial management skills have a positive and significant effect on business success and entrepreneurial motivation. However, entrepreneurial motivation does not significantly mediate the effect of financial management skills on business success. This study confirms the importance of financial management skills in the success of students' businesses, although there are other factors that also contribute.